2021
DOI: 10.21037/tlcr-21-896
|View full text |Cite
|
Sign up to set email alerts
|

The combination of computed tomography features and circulating tumor cells increases the surgical prediction of visceral pleural invasion in clinical T1N0M0 lung adenocarcinoma

Abstract: Background: Visceral pleural invasion (VPI) is a clinical manifestation associated with a poor prognosis, and diagnosing it preoperatively is highly imperative for successful sublobar resection of these peripheral tumors. We evaluated the roles of computed tomography (CT) features and circulating tumor cells (CTCs) for improving VPI detection in patients with clinical T1N0M0 invasive lung adenocarcinoma.Methods: Three hundred and ninety-one patients were reviewed retrospectively in this study, of which 234 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…It follows the "seeds and soil" hypothesis, which states that successful metastasis depends not only on tumor-related factors ("seeds"), but also on the target organ microenvironment ("soil") [11]. The CT imaging features [12,13], histological subtypes [14], genomic alterations [15,16], clinical stage, T stage, and N stage [14] are primary tumor-related factors, and they can re ect invasiveness. They may affect the distribution of BMs.…”
Section: Introductionmentioning
confidence: 99%
“…It follows the "seeds and soil" hypothesis, which states that successful metastasis depends not only on tumor-related factors ("seeds"), but also on the target organ microenvironment ("soil") [11]. The CT imaging features [12,13], histological subtypes [14], genomic alterations [15,16], clinical stage, T stage, and N stage [14] are primary tumor-related factors, and they can re ect invasiveness. They may affect the distribution of BMs.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have proposed combinations of features of the tumor-pleura relationship on computed tomography (CT). These features include direct pleural contact of the tumor, pleural retraction, and pleural tags [ 7 - 10 ]. However, a study by Kim et al [ 7 ], which examined CT-defined VPI and its correlation with disease-free survival in a retrospective review of 695 patients, revealed that approximately one-half of the findings were false positives.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple separate studies have proposed alternative methods for the preoperative assessment of VPI, such as the measurement of circulating tumor cells from serum and pre-resectional pleural lavage tumor cytology. However, these approaches require further research for validation [ 8 , 11 ]. The maximum standardized uptake value (SUVmax) and serum carcinoembryonic antigen (CEA) level have also been identified as significant risk factors for VPI, but no definite cutoff values have been established for diagnosis [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since CTCs are live cells, they can be used in drug screens and functional assays. More importantly, they may predict relapse after primary treatment ( 3 ) even in early stage NSCLC ( 4 ).…”
Section: Introductionmentioning
confidence: 99%